Application of spatial replacement method in the treatment of laparoscopic incarcerated femoral hernia – A case report. (September 2022) - Luo, Binyu; Zhang, Xiao; Guo, Qing; Tian, Yunhong; Ren, Mingyang
Abstract: Introduction: Incarcerated femoral hernia is a common surgical acute abdominal disease. Laparoscopic surgery is considered a safe and effective method for treating incarcerated femoral hernias, which have different surgical approaches to releasing the contents of the hernia. Presentation of case: We report the case of a 65-year-old female with a right incarcerated femoral hernia with an irreducible mass in the right femoral region for 2 days diagnosed by physical examination and abdominal ultrasonography. We used a catheter to inject normal saline into the hernia sac during surgery. Injury and rupture of the small intestine were avoided, and the polypropylene mesh was successfully repaired. Discussion: Incarcerated femoral hernias is a common surgical emergency that can lead to intestinal obstruction, strangulation, or infarction. Laparoscopy is advantageous for treating incarcerated femoral hernias. In our case, spatial replacement theory was used to release the incarcerated small intestine. The principle is that changing the internal and external pressures of the hernial sac returns the hernia contents. The non-necrotic small intestine did not lead to intraperitoneal infection, and the standard transabdominal preperitoneal repair was simultaneously performed with a polypropylene mesh. Conclusion: Laparoscopic incarcerated femoral hernia repair is a common emergency surgery that is safe and feasible for treating incarcerated femoral hernia using the spatial replacement method, the most beneficial to patients. Highlights: Laparoscopic exploration to determine bowel activity in incarcerated femoral hernias Using the space replacement method to successfully release the incarcerated small intestine can avoid iatrogenic intestinal damage The non-necrotic small intestine will not cause intra-abdominal infection, and at the same time use polypropylene mesh for standard TAPP repair to avoid secondary hernia repair